Self-Concept and Social Pressure: A Qualitative Study of Body Image in Adolescent Girls - Abdul Azis; Ahmad Modin; Nafisatun Nadhifah; Zahirah Yaqut Assyifa; Miftahul Huda (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2025)
Increasing social pressure and the influence of the media on beauty standards have created significant challenges for adolescent girls in forming a positive self-concept, especially related to perceptions of body image. Dissatisfaction with physical appearance is common and risks having a negative impact on their mental health and psychological well-being. This research aims to understand in depth how adolescent girls interpret their experiences regarding self-concept and social pressure in shaping body perception. Using a qualitative approach through phenomenological studies, this research explores the subjective narratives of adolescent girls through in-depth interviews to identify thematic patterns that emerge from their experiences. The research results reveal that social pressure originating from peers, family and the media has a strong influence in shaping teenagers' body image and self-concept, both constructively and detrimentally. The participants' narratives also highlighted the importance of social support and self-acceptance as protective factors in building a healthy body image. These findings emphasize the need for education and counseling-based interventions to strengthen adolescents' self-concept and ability to deal with social pressure adaptively.